Synthesis of low-oxidation-state germanium clusters comprising a functional anchor group – synthesis and characterization of [(Ge0)5(Ge-R)3(Ge-(CH2)n-CHCH2)] with R = Si(SiMe3)3. Issue 10 (7th February 2018) - Frischhut, Sabine; Fässler, Thomas F.
Abstract : The first alkenyl-functionalized, uncharged deltahedral germanium clusters [{Si(SiMe3 )3 }3 Ge9 (CH2 ) n CHCH2 ] ( n = 1 or 3) comprising five Ge 0 atoms are presented. Abstract : The first alkenyl-functionalized, uncharged deltahedral germanium clusters [{Si(SiMe3 )3 }3 Ge9 (CH2 ) n CHCH2 ] ( n = 1 or 3) comprising five Ge 0 atoms are presented. All compounds were NMR-spectroscopically and mass-spectrometrically characterized. [{Si(SiMe3 )3 }3 Ge9 (CH2 )3 CHCH2 ] was further characterized by X-ray structure analysis and Raman spectroscopy. Temperature-dependent NMR studies reveal dynamic behavior for both compounds in solution at room temperature. The propenyl derivative [{Si(SiMe3 )3 }3 Ge9 CH2 CHCH2 ] undergoes fast decomposition in solution. The possibility of the comparatively stable pentenyl-substituted Ge9 cluster as a candidate for follow-up reactions is highlighted.